Lipid Peroxidation and in vivo Antioxidant Effect of Various Extracts of Whole Plant of Bridelia scandens in CCl4 Induced Hepatotoxicity Rats - Senthil Kumar, D.; Kottai Muthu, A.; Manavalan, R. (Asian Journal of Chemistry, 2012)
The objective of the present investigation was to evaluate the lipid peroxidation and in vivo antioxidant effect of various extracts of whole plant of Bridelia scandens in CCl4 induced rats. Carbon tetrachloride treated rats were showed significantly (P < 0.001) reduced the levels of tissues enzymatic antioxidant and enhanced the level of non enzymatic antioxidant (glutathione). The level of TBARS are elevated in CCl4 teated rats (group II) when compared with group I (control). The methanolic extract of Bridelia scandens in CCl4 treated rats were found lowered the concentration of TBARS when compared with CCl4 treated rats. Carbon tetrachloride induces the oxidative stress in cell by producing reactive oxygen species. After administration of methanolic extract of Bridelia scandens in CCl4 treated rats were showed significantly (P < 0.001) increased the levels of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR) and reduced the level of non enzymatic antioxidant glutathione (GSH) when compared with CCl4 induced rats (group II). Based on the results, it was concluded that the methanolic extract of Bridelia scandens is a significant source of natural antioxidant, which might be helpful in preventing the progress of various oxidative stresses.